2012
DOI: 10.1177/1753193411428995
|View full text |Cite
|
Sign up to set email alerts
|

Avascular osteonecrosis of the scaphoid (Preiser’s disease) in a 13-year-old boy treated with vascularized bone graft

Abstract: ReferencesAl Hoqail RA. Ultrathin oblique volar-to-dorsal reverse turnover radial artery perforator-based adipofascial flap: a new surgical strategy for reconstructing a Figure 2. One year after the operation. The range of motion of the index finger is 90° for MCP flexion, 45° for MCP extension, 100° for PIP flexion, 0° for PIP extension, 80° for DIP flexion, 0° for DIP extension. All the range of motion for thumb, middle, ring, and little finger is normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The treatment for Preiser disease in children is unclear. We found four cases of Preiser disease in children [ 18 21 ]. One patient treated with a vascularised bone graft showed improvement in both clinically and radiologically [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment for Preiser disease in children is unclear. We found four cases of Preiser disease in children [ 18 21 ]. One patient treated with a vascularised bone graft showed improvement in both clinically and radiologically [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found four cases of Preiser disease in children [ 18 21 ]. One patient treated with a vascularised bone graft showed improvement in both clinically and radiologically [ 21 ]. Two patients treated with immobilisation showed a good clinical course [ 18 , 20 ], and the last patient had no mention of the treatment [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Waters and Stewart achieved union and good function with vascularized bone grafting and internal fixation after failure of immobilization [ 3 ]. Barthel et al reported one case of AVN treated with vascularized bone grafting and internal fixation, obtaining union and pain relief [ 1 ]. The initial diagnosis and management in these studies were based on signal loss of the scaphoid on MRI T1 [ 2 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cases of avascular necrosis (AVN) of the scaphoid are very rare with only six cases regarding the management of AVN in children reported [ 1 3 ]. Because of the limited reports there is currently no consensus when conservative or operative treatment is indicated.…”
Section: Introductionmentioning
confidence: 99%